High Quality of Care Persists With Shifting Depression Services From VA Specialty to Integrated Primary Care. Issue 8 (August 2019) - Leung, Lucinda B.; Escarce, José J.; Yoon, Jean; Sugar, Catherine A.; Wells, Kenneth B.; Young, Alexander S.; Rubenstein, Lisa V.
Abstract : Background/Objective: Offering depression collaborative care services in primary care (PC) settings can reduce use of nonintegrated mental health care resources and improve mental health care access, particularly for vulnerable PC patients. Tests of effects on depression care quality, however, are needed. We examined overall quality of depression care and tested whether increasing clinic engagement in Veterans Affairs (VA)'s Primary Care-Mental Health Integration (PC-MHI) services was associated with differences in depression care quality over time. Methods: We conducted a retrospective longitudinal cohort study of 80, 136 Veterans seen in 26 Southern California VA PC clinics (October 1, 2008–September 30, 2013). Using multilevel regression models adjusting for year, clinic, and patient characteristics, we predicted effects of clinic PC-MHI engagement (ie, percent of PC patients receiving PC-MHI services) on 3 VA-developed longitudinal electronic population-based depression quality measures among Veterans newly diagnosed with depression (n=12, 533). Results: Clinic PC-MHI engagement rates were not associated with significant depression care quality differences. Across all clinics, average rates of follow-up within 84 or 180 days were, 66.4% and 74.5%, respectively. Receipt of minimally appropriate treatment was 80.5%. Treatment probabilities were significantly higher for vulnerable PC patients (homeless: 4.5%, P =0.03; serious mental illness: 15.2%, P <0.001), than for otherwise similar patients without these characteristics. Conclusions/Policy Implications: Study patients treated in PC clinics with greater PC-MHI engagement received similarly high quality depression care, and even higher quality for vulnerable patients. Findings support increasing use of PC-MHI models to the extent that they confer some advantage over existing services (eg, access, patient satisfaction) other than quality of care.